Penerapan Model Multi Channel Single Phase dalam Optimisasi Layanan Restoran Cepat Saji - Nurahmadiningsi Nurahmadiningsi; Nadia Manurung; Nico Dhemus; Dinda Setyasari; Dittha Kumari; Ni Ketut Tari Tastrawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
A queue is a waiting line from a service facility. Long queues are caused by the number of consumers who come more than the number of service facilities, it is necessary to apply a queuing model to overcome long queues. This research was conducted at Mc Donald's Jimbaran fast food restaurant because the fast food restaurant is located in a tourist and lecture area, causing queues. The current condition at Mcdonald’s Jimbaran there are more than one service facility, the discipline of the first come first service (FCFS) queue is in accordance with the single-phase multi-channel. After analyzed with data from 31 May 2022 to 06 June 2022 for 7 days. Based on the results of the analysis obtained, it can be concluded that at lunch time requires 4 services while at dinner time only requires 2 service.